A Statistical Study of Pi2 Pulsations Observed in the Upper Ionosphere Using Swarm Magnetic Field Data. Issue 1 (11th January 2020) - Park, Jae‐Hee; Kim, Khan‐Hyuk; Kwon, Hyuck‐Jin; Jee, Geonhwa; Hwang, Junga
Abstract: The properties of Pi2 pulsations observed in the upper ionosphere are studied using magnetic field data acquired by the Swarm A spacecraft in low Earth orbit and at the low‐latitude Bohyun ground station (BOH, L =1.3) for January 2014 to June 2015. From time intervals when Swarm A was on the nightside (magnetic local time (MLT) = 1800–0600 hr) and the BOH station was near midnight (MLT = 2100–0300 hr), we identified 621 Pi2 events in the horizontal H component of the BOH data. For each event we examined the coherence between the horizontal H component on the ground and the B x (radial), B y (azimuthal), or B z (compressional) components at Swarm A. Out of 621 events, the B x − H high‐coherence (> 0.7) events are ∼6%, the B y − H high‐coherence events are ∼2%, and the B z − H high‐coherence events are ∼25%. The ground satellite high‐coherence events occurred when the spacecraft was located at magnetic latitudes between −50° and 50°. Using the ground satellite high‐coherence events, we statistically examined the latitudinal structure of the relative amplitude and phase of the ionospheric Pi2 pulsations and found that their latitudinal variations is consistent with the north‐south mode structure expected from the plasmaspheric resonance model. Our statistical results indicate that the source of ionospheric Pi2 pulsations is the plasmaspheric resonance. Key Points: The ground satellite high coherence occurs when the spacecraft was located at |MLAT| ≤ 50° The latitudinal structure of the relative amplitude and phase of the ionospheric Pi2 pulsations are examined The source of ionospheric Pi2 pulsations is the plasmaspheric resonance